Genipin‐crosslinked collagen scaffolds inducing chondrogenesis: a mechanical and biological characterization. Issue 7 (9th March 2022) - Scialla, Stefania; Gullotta, Fabiana; Izzo, Daniela; Palazzo, Barbara; Scalera, Francesca; Martin, Ivan; Sannino, Alessandro; Gervaso, Francesca
Abstract: Articular cartilage degeneration is still an unsolved issue owing to its weak repairing capabilities, which usually result in fibrocartilage tissue formation. This fibrous tissue lacks of structural and bio‐mechanical properties, degrading over time. Currently, arthroscopic techniques and autologous transplantation are the most used clinical procedures. However, rather than restoring cartilage integrity, these methods only postpone further cartilage deterioration. Therefore, tissue engineering strategies aimed at selecting scaffolds that remarkably support the chondrogenic differentiation of human mesenchymal stem cells (hMSCs) could represent a promising solution, but they are still challenging for researchers. In this study, the influence of two different genipin (Gp ) crosslinking routes on collagen (Coll )‐based scaffolds in terms of hMSCs chondrogenic differentiation and biomechanical performances was investigated. Three‐dimensional (3D) porous Coll scaffolds were fabricated by freeze‐drying techniques and were crosslinked with Gp following a " two‐step " and an in " bulk " procedure, in order to increase the physico‐mechanical stability of the structure. Chondrogenic differentiation efficacy of hMSCs and biomechanical behavior under compression forces through unconfined stress–strain tests were assessed. Coll /Gp scaffolds revealed an isotropic and highly homogeneous pore distribution along with an increase in the stiffness, also supported by the increase in the Coll denaturation temperature ( T d = 57–63°C) and a significant amount of Coll and GAG deposition during the 3 weeks of chondrogenic culture. In particular, the presence of Gp in " bulk " led to a more uniform and homogenous chondral‐like matrix deposition by hMSCs if compared to the results obtained from the Gp " two‐step " functionalization procedure. Abstract :